Capacitismo: Vontade de verdade e estratégias de resistência - Oliveira Júnior, Kennedy José de (2024)
The main objective of this research is to investigate the conditions of possibility for the emergence of the concept of ableism in the Brazilian academic-scientific scenario. We also aim to understand the wills of truth and resistance strategies within the constitution of discursive plots about bodies with disabilities, in addition to analyzing the dynamics of institutional power through the establishment of norms that control scientific practices involving human subjects. We recognize the existence of systems of oppression and (in)visibility regarding the demands of research conducted with subjects with disabilities, given the socio-historical silencing of corporealities located in the wake of monstrosity (abnormality) and the subjection of research to biomedical conceptions. The theoretical foundation of this research is primarily based on the reflections of Michel Foucault (1979; 1987; 2010; 2020; 2021) on power relations among subjects, discourse, statement, and discursive formations; as well as theories about truth, abnormality, resistance, and the history of human sciences. To discuss disability and ableism, we rely on authors such as Diniz (2007), Campbell (2001; 2009), Deleuze (2000), among others. This research is characterized as a study within archaeogenealogy. To conduct the research, we selected the article "Disability, Incapacity, and Vulnerability: From Ableism or the Preeminence of Ableism and Biomedicine in the Research Ethics Committee of UFSC," by researcher Anahí Mello, published in the journal Ciência e Saúde Coletiva, with a Qualis A1 rating, with the aim of analyzing how the UFSC research ethics committee understands studies involving human subjects, especially those with disabilities. The analyses revealed that the concept of ableism emerges as a will of truth and resistance to hegemonic research domains, and also demonstrate that studies on ableism are incipient in various fields of knowledge, particularly in Foucauldian Discursive Studies.